Antecedents of environmental strategies: a study of the manufacturing industry in Pakistan - Saleem, Farida; Zhang-Zhang, Yingying; Gopinath, C.; Malik, Muhammad Imran (International journal of emerging markets, 2023)
PurposeThe paper aims to explore how market pressures, upper echelons theory and slack resources interact to affect pro-environmental strategies in an emerging market. Specifically, the authors assess external market factors (consumer concerns, regulatory forces and competitors' concerns) in terms of how they are negotiated through internal resources and company capabilities (top management commitment and discretionary slack) to produce or not produce pro-environmental strategies (environmental corporate strategy and environmental marketing strategy).Design/methodology/approachA total of 1,000 questionnaires were distributed in the Pakistani manufacturing sector – where energy use and natural resources consumption is intensive. The final 181 useable responses were analyzed using covariance-based structural equation modeling and the PROCESS macro.FindingsThe results reveal that regulatory forces and competitors' concerns have both direct and conditional indirect effects on environmental corporate strategy but only conditional indirect effects on environmental marketing strategies through the mediation of top management commitment and at different levels of discretionary slack. However, consumer concerns remain inconsequential antecedents with insignificant direct effects and conditional indirect effects on environmental corporate and marketing strategies through the mediation of top management commitment at different levels of discretionary slack.Originality/valueThe authors propose an integrative model as a functioning mechanism for the environmental strategic decisions of companies in emerging markets. This model relies on both slack resource and upper echelons theories. These findings contribute to a better understanding of the impacts of internal and external determinants and functions on environmental strategies at corporate and functional levels in emerging markets. The various paths to diverse levels of environmental strategy and the insignificant role of consumer concerns suggest a need for further investigation of corporate environmentalism in emerging markets that consider their distinctive legal, societal, market and institutional contexts.